1970
DOI: 10.1163/156853970x00321
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of Conspecific Aggressive Responses in the Siamese Fighting Fish (Betta Splendens)

Abstract: Mature male Siamese fighting fish (Betta splendens) were presented with a conspecific male confined in a clear plastic tube for either 15 minutes per day for 20 days (group E 15) or 60 minutes per day for 5 days (group E 60). A third group was presented with this aggression eliciting conspecific male stimulus for 15 minutes on days 1 and 2 and again on days 19 and 20. This group (group C 15) was designed to control for post-stimulation waning of aggressive behaviors independent of constant stimulation and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 1 publication
3
21
0
Order By: Relevance
“…The responsiveness then wanes until after 5 min exposure to the mirror; the duration of gill-cover erection is less than when there is no mirror exposure at all. This waning in responsiveness is in agreement with earlier reports of habituation of aggression in this species (Baenninger, 1966;Clayton & Hinde, 1968;Figler, 1972;Meliska & Meliska, 1976;Peeke & Peeke, 1970), although for most of these earlier studies much longer periods of exposure were needed to demonstrate habituation. The much shorter exposures needed for the reduction of responsiveness in the present experiment might 300 -.. odel).…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…The responsiveness then wanes until after 5 min exposure to the mirror; the duration of gill-cover erection is less than when there is no mirror exposure at all. This waning in responsiveness is in agreement with earlier reports of habituation of aggression in this species (Baenninger, 1966;Clayton & Hinde, 1968;Figler, 1972;Meliska & Meliska, 1976;Peeke & Peeke, 1970), although for most of these earlier studies much longer periods of exposure were needed to demonstrate habituation. The much shorter exposures needed for the reduction of responsiveness in the present experiment might 300 -.. odel).…”
Section: Methodssupporting
confidence: 91%
“…Despite the shortness of the tests, there was significantly less gill-cover erection on the 1st day than on any other of the 6 experimental days, no matter which model was used. Most previous studies have shown a long-term decrease in responsiveness (e.g., Gallagher, Herz, & Peeke, 1972), even when only relatively short periods of exposure were given on each day (Peeke & Peeke, 1970). However, Clayton and Hinde (1968) did show that the duration of gill-cover erection (the measure used here) increased over the first 24 h of continuous mirror exposure, although they did not say whether this increase was statistically significant.…”
Section: Methodsmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, animals which exhibited submissiveness (zero display rates) during mutually caged encounters significantly increased the intensity of aggression during subsequent mutual viewing, while the dominant caged mates decreased the rate of displays. These results were interpreted to mean that mutual viewing produces habituation while mutual caging produces conditioned suppression, and that generalizations from one situation to the other may therefore be unwarranted.On the basis of Simpson's (1968) findings, Peeke and Peeke (1970) have criticized the use of mirror images as releasing stimuli in the study of Betta splendens (Siamese fighting fish). They suggest that the sequential and spatial relationships which characterize Betta aggressive behavior outside of the laboratory would be for the most part precluded by the use of mirror images.…”
mentioning
confidence: 99%